Comparative evaluation of desensitizing agents on shear bond strength of zirconia to dentin - İrem Çötert; Merve Aytuğ; H. Serdar Çötert (BMC, 2024)
Abstract Background The purpose of the study is to evaluate the effect of 7 different desensitizing agents on the shear bond strength (SBS) of zirconia restorations to dentin with a self-adhesive resin cement and determine the failure modes. Methods Eighty molars' occlusal surfaces were ground to expose dentin and were randomly divided into 8 groups (n = 10): 1. Gluma (HEMA/Glutaraldehyde) 2. Bifluoride (Sodium Fluoride/Calcium Fluoride) 3. Admira (Bis-GMA/HEMA) 4. Smart Protect (Glutaraldehyde) 5. Teethmate (Tetracalcium phosphate, Dicalcium phosphate) 6. Clinpro White (Sodium fluoride) 7. BisBlock (Oxalic acid) and 8. Control (No-treatment). After applying the agent, a self-adhesive resin cement (Rely-X U200) was used to lute zirconia discs (4 mm height and 4 mm diameter) to dentin. After stored in distilled water at 37 °C for 24 h, all groups were thermocycled for 2500 cycles between 5 ± 2 °C and 55 ± 2 °C. Specimens were submitted to SBS test with a universal testing machine at a crosshead speed of 0.5 mm/min until failure. SBS values were compared with ANOVA. Post-hoc multiple comparisons were performed with Dunnett T3. The failure modes of specimens were examined with stereomicroscope at a magnification of 20X and the distribution of the failure modes were evaluated with Pearson Chi-Square test. Results Regarding mean SBS values in MPa's; Admira (10.70 ± 3.99), Smart Protect (9.62 ± 3.93), and Gluma (8.90 ± 3.76) treatments showed higher SBS values compared to control group (p < .05) according to ANOVA. The SBS values of Teethmate (5.31 ± 2.37) and Clinpro White (4.32 ± 2.44) were higher than control group but the difference was not found significant (p > .05). BisBlock (2.33 ± 1.94) and Bifluouride (1.60 ± 1.47) groups showed the lowest SBS values but their difference between control group was not found statistically significant (p > .05). Most specimens showed adhesive failure but no statistically significant difference was found in the distributions of failure modes according to Chi-square test. Conclusion Within the limitation of the study; Admira, Smart Protect, and Gluma increased the SBS of the zirconia restorations to dentin and can be recommended to use on prepared dentin surfaces prior to the cementation.